2018
DOI: 10.2474/trol.13.188
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Characteristics of Friction Brake Material Using Cantala Fibers as Reinforcement

Abstract: Friction brake materials are made from a mixture of materials with different properties in order to meet the brake performance requirement. Friction brake material contains a reinforcement fiber that serves to maintain the integrity of the material when subjected to loading. Natural fiber has the potential to be used as a reinforcement material for friction material due to some of its superior characteristics. In this research, friction brake materials using cantala fibers were developed to investigate their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A correct tribo-film must be formed on the friction-pair interface when working with grains and could reproduce tribo-film, stabilizing the friction coefficient. Usually, vital lubricant includes many metal sulphides including, di-sulphide of molybdenum, sulphide, antimony, iron sulphide, sulphide of copper, etc., as well as numerous graphite forms, such as natural graphite, flake, synthetic and polarized graphite [45][46][47].…”
Section: Mechanical and Materials Characteristicsmentioning
confidence: 99%
“…A correct tribo-film must be formed on the friction-pair interface when working with grains and could reproduce tribo-film, stabilizing the friction coefficient. Usually, vital lubricant includes many metal sulphides including, di-sulphide of molybdenum, sulphide, antimony, iron sulphide, sulphide of copper, etc., as well as numerous graphite forms, such as natural graphite, flake, synthetic and polarized graphite [45][46][47].…”
Section: Mechanical and Materials Characteristicsmentioning
confidence: 99%
“…Generally speaking, from the macro-perspective, reinforced fibers have a high modulus, high strength, and good thermal and tribological stability, which can be used to enhance strength, fade resistance (the resistance of the friction coefficient (COF) to high-temperature reduction), and wear resistance [ 9 ]. From the micro-perspective, reinforced fibers play a positive role in consolidating wear debris, and they are the primary plateau, which can produce nucleation of wear debris, thus promoting the formation of a secondary plateau [ 10 , 11 , 12 ]. Commonly used reinforced fibers include metal fiber (such as steel fiber and copper fiber, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed the ability of the inclusion of Cantala fiber into polymer matrix to increase the resistance against wear and maintain the coefficient of friction of the composites. [ 26 ] The characterization of 6% NaOH treated A. Cantala fiber and microcrystalline cellulose reinforced polyester composites were evaluated by Sakuri et al [ 27 ] The results showed the chemically treated fiber reinforced composite having higher thermal stability than untreated one with a crystallinity index (CI) of 73.65% after alkali‐treatment.…”
Section: Introductionmentioning
confidence: 99%